Identification and integrated analysis of glyphosate stress-responsive microRNAs, lncRNAs, and mRNAs in rice using genome-wide high-throughput sequencing - Rongrong Zhai; Shenghai Ye; Guofu Zhu; Yanting Lu; Jing Ye; Faming Yu; Qiren Chu; Xiaoming Zhang (BMC Genomics, 2020)
Abstract Background Glyphosate has become the most widely used herbicide in the world. Therefore, the development of new varieties of glyphosate-tolerant crops is a research focus of seed companies and researchers. The glyphosate stress-responsive genes were used for the development of genetically modified crops, while only the EPSPS gene has been used currently in the study on glyphosate-tolerance in rice. Therefore, it is essential and crucial to intensify the exploration of glyphosate stress-responsive genes, to not only acquire other glyphosate stress-responsive genes with clean intellectual property rights but also obtain non-transgenic glyphosate-tolerant rice varieties. This study is expected to elucidate the responses of miRNAs, lncRNAs, and mRNAs to glyphosate applications and the potential regulatory mechanisms in response to glyphosate stress in rice. Results Leaves of the non-transgenic glyphosate-tolerant germplasm CA21 sprayed with 2 mg·ml− 1 glyphosate (GLY) and CA21 plants with no spray (CK) were collected for high-throughput sequencing analysis. A total of 1197 DEGs, 131 DELs, and 52 DEMs were identified in the GLY samples in relation to CK samples. Genes were significantly enriched for various biological processes involved in detoxification of plant response to stress. A total of 385 known miRNAs from 59 miRNA families and 94 novel miRNAs were identified. Degradome analysis led to the identification of 32 target genes, of which, the squamosa promoter-binding-like protein 12 (SPL12) was identified as a target of osa-miR156a_L + 1. The lncRNA-miRNA-mRNA regulatory network consisted of osa-miR156a_L + 1, two transcripts of SPL12 (LOC_Os06g49010.3 and LOC_Os06g49010.5), and 13 lncRNAs (e.g., MSTRG.244.1 and MSTRG.16577.1). Conclusion Large-scale expression changes in coding and noncoding RNA were observed in rice mainly due to its response to glyphosate. SPL12, osa-miR156, and lncRNAs (e.g., MSTRG.244.1 and MSTRG.16577.1) could be a novel ceRNA mechanism in response to glyphosate in rice by regulating transcription and metal ions binding. These findings provide a theoretical basis for breeding glyphosate-tolerant rice varieties and for further research on the biogenesis of glyphosate- tolerance in rice.